LEXICAL EXPRESSIVE LAYER OF LANGUAGE - Khakimova Farangiz Nadirovna (Journal Park Publishing, 2023)
The given article discusses one of the emotional aspects of language is expressed in what layers of language the author uses in a particular work, how and in what way and this is related to style. The main goal of linguistic and cultural studies, as an auxiliary discipline for the practical mastering of the language, and therefore a subject of philological orientation, is to ensure understanding, namely: the transfer of knowledge of culture, the so-called background knowledge, contributing to the full disclosure of the meaning of the statement and its adequate understanding in the act of communication in English and Russian languages.
Keywords: style, emotional aspects, literary translation, specific linguistic tools, archaism.